PENGARUH PERENCANAAN STRATEGI DAN PENGENDALIAN INTERN TERHADAP KINERJA KARYAWAN - Latifa, Tadzkirotul; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out the influence of strategy planning and internal control to the employee performance of PT Kereta Api Indonesia (Persero) DAOP 8 Surabaya. If the strategy planning can determine the success of an organization, so that it is expected that internal control canencourage the employees to improve the quality of employee performance. The population is 50 employees who work at PT Kereta Api Indonesia (Persero) DAOP 8 Surabaya. This research is a quantitative research. Mean while,the analysis method has been conducted by using multiple linear analysis with F test and multiple determination coefficient, and the hypothesis test has been done by using t test. The result of the research shows that strategy planning (Ps) give significant and positive influence to the employees performance (Kk), it is proven by the result of the t test shows that t count is 2.213 with its significance value is 0.032 < 0.05 and internal control (Pi) give significant and positive influence to the employee performance (Kk), this can be seen by using t test shows that t count value 5.980 with its significance value is 0.000 < 0.05.Keywords: Strategy planning, internal control, employee performance.